India's China policy : strategic shift or a drift? - Suryanarayana, Pisupati Sadasiva (2021)
Successful disengagement by the confronting Chinese and Indian soldiers at a key site along their disputed frontier in February 2021 is optimistically seen as a pause for peace. It is time for India to choose to remain an autonomous player or become a frontline-state in a US-led coalition focused on China.